Special Facilities in Elementary School Laboratories: Characteristics and Physical Components that Support Learning - Sherly Dwi Amelia; Junaidin (Mataram University, 2026)
This study aims to examine specialized laboratory facilities in elementary schools, focusing on their physical characteristics and components in supporting student learning. The background of this study is based on the importance of a learning environment that is appropriate for the developmental stage of elementary school students, who are still in the concrete operational stage and therefore require learning experiences that are hands-on, contextual, and interactive. Emerging issues indicate that laboratory facilities in elementary schools are often not optimally designed, whether in terms of accessibility, simplicity, or visual appeal, and thus fail to sufficiently support student engagement in learning. This study employs a descriptive qualitative approach using a literature review method. Data were obtained from various academic sources such as books, scientific journals, and educational policy documents, and were then analyzed using content analysis techniques to identify key themes related to laboratory facilities. The results of the study indicate that elementary school laboratory facilities need to be accessible, simple, functional, visually appealing, and flexible. Supporting physical components include student work areas, open storage, educational displays, exploration corners, and adequate lighting and ventilation. Well-designed facilities contribute to students’ comfort and engagement in learning, thereby playing a crucial role in creating an effective and meaningful learning environment.